The Essence Of Mahabbah In The Context Of Modern Tasawufic Morals - Afifah, Yuli Siti Nur (STAI Darussalam Kunir, 2025)
The phenomenon of the crisis of understanding the meaning of love has hit the modern generation. Many young men and women are found to interpret love/mahabbah only to fellow creatures, so that many ignore morals to Allah as a creator who deserves to be loved. Therefore, further research is needed regarding the essence of mahabbah as one of the morals and ahwal in the science of Sufism in this modern era. This research is based on a descriptive qualitative method with a library research approach, namely research that examines and seeks information and data that as a whole comes from written language that is related and relevant to the title being studied. The analysis method used is descriptive-analytical analysis, namely analyzing and drawing conclusions from reading materials that are used as references while also seeing relevant relationships. The results of this study indicate that modern Sufism is actually a term in the world of Sufism that was born in the century of modernization. This term is used for society to be able to accept the teachings of Sufism. Because in essence the essence of modern Sufism and previous Sufism is the same, namely a discipline in Islam that studies the spiritual aspects and mystical life. The essence of mahabbah with the morals of modern Sufism is so that the Islamic community remains on the path that is pleasing to Him, is able to maintain the morals of its actions from things that exist and was born in an era full of progress.